THE COMMUNICATION STRUCTURE OF THE UKRAINIAN INFORMATION FLOWS ABOUT THE CRIMEA DEVELOPMENT AS A PART OF RUSSIA: SOCIAL-MEDIA ANALYTICS AND DISCOURSE ANALYSIS - Elena V. Brodovskaya; Anna Y. Dombrovskaya; Dmitry N. Karzubov (Вестник Московского государственного областного университета, 2018)
The article presents the results of a comprehensive study of the characteristics of Ukrainian social and media flows about the Crimea development in Russia. The design of the study includes an automated analysis of the content of social media messages using special software and discursive analysis of relevant social media documents. Four types of information flows of the Ukrainian network leaders are identified. They form anti-government settings among the Crimean and Russian users. The specific weight of these flows in the structure of social and media space is defined. The technological, structural and substantive characteristics of the most significant and influential Ukrainian flows aimed at constructing discourses of Russian aggression and illegitimacy of political decisions of the Russian authorities are analyzed. The largest social media stream is dedicated to the “Russian aggressive position” discourse, the dynamic of this flow is quite stable in social media “VKontacte” during 2014 - 2018. Both the titles of the most influential blogs and the tags of the flows reflect the idea of war between Ukraine and Russia. The paper provides the new body of empirical data on the social media space segmentation and share the unique method of search for the Internet content.